Convenience and risk factors affecting mobile banking adoption behavior: the mediating role of trust/ Sukjeet Sandhu ... [et al.] - Sandhu, Sukjeet; Kai, Jin; Maity, Ritwik; Saad, Abidah; Syed Abu Bakar, Syarifah Mastura; Singh, Harpajan (Universiti Teknologi MARA Selangor, 2022)
In this digital age, major financial institutions have given mobile banking a huge amount of publicity and are promoting it aggressively. Previous research has revealed, however, that mobile banking use among young adults is still in its early stages and has yet to gain widespread acceptance. These youths do not have a strong knowledge of mobile banking and are apprehensive about its security. Therefore, this paper aims to investigate the factors that affect mobile banking usage intention. We administered a survey to 363 university students and analyzed the collected data using statistical software. The research results show that perceived convenience and perceived risks have a significant impact on intention of mobile banking. In addition, customer trust plays a mediator in this linkage. The results of this study provide a scientific basis for the further development of mobile banking. Besides, the expansion of mobile banking business should strengthen technological innovation, enrich the range of functions of mobile banking, reduce the risks, and improve user experience. Banks and mobile operators should strengthen cooperation to build a safe mobile banking operating system platform, improve service quality, and provide customers with better financial business support.